2018
DOI: 10.1016/j.seizure.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and recurrence of Takotsubo syndrome: One clinical presentation and trigger, but two different anatomical variants in the same patient. A case to meditate on

Abstract: We present the case of a 67-year-old woman affected by hypertension and hypercholesterolemia. She had a history of alcoholism, anxiety disorder with panic attacks, and paroxysmal atrial fibrillation. Despite a previous transient ischemic attack and her thromboembolic risk (CHA 2 DS 2 -VASc score: 5), she had not been taking anticoagulants at home without a reasonable motivation. Moreover, around eighteen years prior, she had breast cancer and underwent surgical intervention, radiotherapy and several years of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…We appreciated the Letter to the Editor by Professor Finsterer concerning our case report previously published in this Journal [1,2].…”
Section: Replymentioning
confidence: 85%
See 1 more Smart Citation
“…We appreciated the Letter to the Editor by Professor Finsterer concerning our case report previously published in this Journal [1,2].…”
Section: Replymentioning
confidence: 85%
“…
ReplyRecurrent seizure-triggered Takotsubo: A suggestive differential diagnosisWe appreciated the Letter to the Editor by Professor Finsterer concerning our case report previously published in this Journal [1,2].In his letter, Professor Finsterer proposes a mitochondrial disorder as a possible cause for the scenario presented by our patient. However, the patient, a 67-year-old woman, did have any other clinical signs supporting this suggested diagnosis (e.g.
…”
mentioning
confidence: 76%
“…There have been reports of TS after seizures in the literature. 11 , 12 In fact, a large nationwide population-based study with 981 571 cases of epilepsy-related hospitalizations, showed that the rate of TS in these patients was 1 in 1000 and showed poor inpatient outcomes. 13 In addition, females with a neurological diagnosis appear to be at higher risk of developing TS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to some data, in 37% of patients with TS, the onset of syndrome was preceded by mental illness [ 96 ]. A TS trigger may be status epilepticus [ 97 , 98 ] or convulsions of a different origin [ 99 - 101 ]. In this regard, it should be noted that bicuculline-induced status epilepticus is accompanied by an increase in the plasma norepinephrine level in dogs [ 102 ].…”
Section: Etiology Of Takotsubo Syndromementioning
confidence: 99%